Seven Spirits from Patmos: Towards a Decolonial Chinese Theology for the Third Millennium - FENG, Jacob Chengwei (Journal of Research for Christianity in China (JRCC), 2023)
Compared to the five centuries of global colonial history, China’s colonial history lasted only one hundred and nine years (1840-1949). However, since 1949, coloniality, anti-colonialization, anti-imperialism, and decolonization have been deeply embedded in Chinese theology while lurking in ideology, philosophy, and politics. This paper argues that Chinese theology faces a grave epistemic crisis and needs to be transformed epistemologically by appealing to the seven spirits of God and shifting to decolonial thinking in the global decolonial discourse. This paper first analyzes China's (semi-)colonial/anti-colonial history in four stages with its various influences on Chinese theology. Then the paper adopts a three-layered “sandwich” approach to expose the profound epistemic crisis that is deeply submerged in Chinese theology. Finally, based on Witness Lee and Amos Yong’s pneumatology, the paper proposes a decolonial Chinese theology for the third millennium.